Adaptations and responses of the common dandelion to low atmospheric pressure in high‐altitude environments. (19th July 2021) - Arce, Carla C. M.; Bont, Zoe; Machado, Ricardo A. R.; Cristaldo, Paulo F.; Erb, Matthias
Abstract: Atmospheric pressure is an important, yet understudied factor that may shape plant ecology and evolution. By growing plants under controlled conditions at different experimental stations in the Swiss alps, we evaluated the impact of ecologically realistic atmospheric pressures between 660 and 950 hPa on the growth and defence of different dandelion populations. Low atmospheric pressure was associated with reduced root growth and defensive sesquiterpene lactone production. Defence suppression only occurred in populations originating from lower altitudes. Populations from higher altitudes constitutively produced less sesquiterpene lactones and did not suffer from suppression under low atmospheric pressure. Synthesis . We conclude that atmospheric pressure modulates root growth and defence traits, and that evolutionary history shapes plant phenotypic responses to atmospheric pressure. Our findings have important implications for our understanding of altitudinal gradients and the future use of plants as a source of food and bioactive metabolites in extraterrestrial habitats. Abstract : We conclude that atmospheric pressure modulates root growth and defence traits, and that evolutionary history shapes plant phenotypic responses to atmospheric pressure. Our findings have important implications for our understanding of altitudinal gradients and the future use of plants as a source of food and bioactive metabolites in extraterrestrial habitats.